Association between autoimmune disease and cutaneous melanoma with regard to melanoma prognosis. (5th December 2014) - Bottoni, U.; Paolino, G.; Ambrifi, M.; Didona, D.; Albanesi, M.; Clerico, R.; Lido, P.; Brachini, A.; Corsetti, P.; Richetta, A. G.; Cantisani, C.; Calvieri, S.
Summary Background An association between autoimmune disease and malignant melanoma (MM) has often been reported in the literature as a positive prognostic factor for MM. Consequently, we evaluated the influence of different autoimmune diseases on the prognosis of MM. Aim To evaluate the prognosis of patients with MM who also had an autoimmune disorder, whether tumour‐associated, paraneoplastic or drug‐induced. Methods Autoimmune diseases were classified and analysed as tumour‐associated, paraneoplastic or drug‐induced. Patients were enrolled according to their clinicopathological features and matched with control groups. Kaplan–Meier analysis was used to estimate disease‐free survival (DFS) and overall survival (OS), and log‐rank test was used to evaluate differences between the survival curves. Results In total, 49 patients with MM and tumour‐associated autoimmune disease were included in our analysis. No case of paraneoplastic autoimmune disease was detected. The survival analyses showed a range of results, from a worsening of DFS and OS to a lack of any difference. In a second analysis, we separately analysed patients who developed autoimmune disorders after starting adjuvant therapy with interferon‐α; we did not find significant differences between these patients and the untreated patients. Conclusions Autoimmune disease, whether tumour‐associated or drug‐induced, was not associated with better prognosis in patients with MM. The results suggest that the reported relationship between autoimmunity and MM may be a result of individual variation in sensitivity to the autoimmune disease, the tumour or the treatments.